A cross-sectional retrospective survey of injury situation and prevalence in female recreational netball players with a focus on knee injuries. (March 2023) - Mullally, Elaine M.; Atack, Alexandra C.; Glaister, Mark; Clark, Nicholas C.; Brown, Nicola
Abstract: Objectives: To examine situations of injury and injury prevalence in female adult recreational netball players with a focus on knee injuries. Design: Cross sectional retrospective online survey. Participants: 193 female adult recreational netball players. Main outcome measures: Any injury sustained in the previous 12 months, situation of injury, any knee injuries sustained in the previous five years, the length of time unable to play netball, and knee injury management. Results: In the previous 12 months, 61% of respondents sustained injury to the lower limb, and 27% to the upper limb. Lower limb injury situations were mostly landings (46%). Upper limb injury situations were mostly collisions with an opponent (27%). 46% reported sustaining a knee injury in the previous five years. Following knee injury, players were unable to play netball for 6.8 ± 7.0 months (training); and 8.2 ± 7.4 months (matches) respectively. Conclusions: Lower limb injury is more common than upper limb injury in recreational adult female adult netball players. Landing was the most common situation of injury for the lower limb including knee injuries. In the previous five years, nearly half of the players had sustained a knee injury resulting in more than six months out of the game. Highlights: Lower limb injuries remain a concern in female adult recreational netball players. The most common situation of injury is landing. Landing technique must be considered by netball coaches. Current training and injury prevention practices need to be understood. Appropriate IPPs need to be designed and implemented.